Systematic Repressive System: An Analysis of Legal Instruments as a Tool to Silence Criticism by the Indonesian Government - Muhammad Ifan; Titik Sudartinah; Pangesti Wiedarti; Pratomo Widodo; Evi Sulistiana; Azhari Azhari (Universitas Muhammadiyah Malang, 2025)
Citizens who voice criticism of government policies often face criminalization, eroding expressive spaces, and democratic freedoms. This study examines a systematic repressive apparatus enforced through legal instruments. Beyond mere coercive action, it explores how biased language within legislation constructs narratives that legitimize repressive measures. Utilizing the AntConc corpus tool and a Critical Discourse Analysis (CDA) approach, this research analyzes the discourse embedded in the Electronic Information and Transactions Law (ITE Law), the Indonesian Criminal Code (KUHP), the Law on Mass Organizations (UU Ormas), and Government Regulation No. 26 of 2020. The findings reveal that the state constructs a system of negative labeling, framing expressions of dissent as threats to national stability through terms such as “public order disruptor,” “threat to state officials,” “freedom usurper,” and “communism propagator.” These terms function not only as juridical categories, but also as ideological labels that criminalize dissent. Legal language in these documents is applied selectively to reinforce negative perceptions of critics and plays a role in perpetuating structural violence. Therefore, this study emphasizes the urgent need for a critical audit of legal language to eliminate ambiguous and biased terminology.